Sirolimus-based immunosuppression improves the prognosis of liver Transplantation Recipients with low TSC1/2 expression in hepatocellular carcinoma beyond the Milan Criteria. Issue 10 (October 2021) - Ye, Qianwei; Ling, Sunbin; Jiang, Guangjiang; Shan, Qiaonan; Xu, Shengjun; Zhan, Qifan; Wu, Yifeng; Liu, Yuchen; Zheng, Shusen; Xu, Xiao
Abstract: Background: The use of the immunosuppressive agent sirolimus (SRL) following liver transplantation (LT) in patients with hepatocellular carcinoma (HCC) is controversial. Sirolimus is a typical mammalian target of rapamycin (mTOR) inhibitor, and tuberous sclerosis 1-tuberous sclerosis 2 complex (TSC1/TSC2) is an important negative effector in the mTOR pathway. In this study, we investigated the effect of SRL-based immunosuppression on the prognosis of LT recipients with HCC beyond the Milan criteria based on TSC1/2 expression and explored the effect of TSC1 on HCC in vitro and in vivo . Methods: We retrospectively analyzed 120 HCC patients who underwent LT in our hospital between January 1, 2015 and December 30, 2018. All patients had HCC beyond the Milan criteria and were divided into the SRL group (n = 50) and non-SRL group (n = 70). TSC1/2 expression levels in paraffin-embedded tissues were determined by immunohistochemistry (IHC) and then analyzed as subgroups. Overall survival (OS) and disease-free survival (DFS) were analyzed using the Kaplan-Meier method. TSC1 expression was silenced in Huh-7 and Bel-7402 cell lines for further cell function experiments. Results: 88.3% of patients were HBV LT recipients. The SRL group exhibited better DFS and OS compared to the non-SRL group (P = 0.02, P = 0.003). Subgroup (TSC1-based or TSC2-based) analyses revealed that patients with low TSC1 or TSC2 expression benefited from sirolimus (DFS: P = 0.046, OS: P = 0.006 for TSC1; DFS: P = 0.05, OS: P = 0.003 for TSC2) compared with patients with high expression. TSC1 knockdown in Huh-7 and Bel-7402 HCC cell lines activated the mTORC1 pathway and enhanced cell proliferation, migration and sensitivity to SRL in vitro and in vivo . Conclusion: TSC1/2 expression could be used to predict the prognosis of patients with HCC beyond the Milan criteria who underwent SRL-based immunosuppression following LT. TSC1 knockdown promoted HCC malignancy and enhanced sensitivity to SRL. Highlights: SRL could improve outcomes of LT recipients beyond Milan Criteria. TSC1/2 could act as a molecular index to predict the effect of SRL in LT patients. TSC1 knockdown promoted HCC malignancy and enhanced sensitivity to SRL.